2006
DOI: 10.1097/01.ccm.0000242156.15757.70
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed steroid therapy is an effective treatment for intractable hyperemesis gravidarum

Abstract: A short course of hydrocortisone is an effective treatment for intractable hyperemesis gravidarum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 14 publications
0
49
0
2
Order By: Relevance
“…42,58,68,69,73,77,79,82,95,100,105,109,111 Other sources of bias Twenty of the included RCT studies were judged as having low risk of bias in this area. 13,41,42,61,62,64,67,70,71,74,81,83,88,96,[101][102][103]106,110,112 However, a substantial number (n = 44) were classed as unclear, due to lack of sufficient information in the paper to permit detailed assessment of whether or not an important risk of bias existed, or due to insufficient rationale or evidence that an identified problem had introduced serious levels of bias to the study. 43,[57][58][59][60]65,66,68,69,72,73,[75][76][77][78]…”
Section: Allocation Concealmentmentioning
confidence: 99%
See 3 more Smart Citations
“…42,58,68,69,73,77,79,82,95,100,105,109,111 Other sources of bias Twenty of the included RCT studies were judged as having low risk of bias in this area. 13,41,42,61,62,64,67,70,71,74,81,83,88,96,[101][102][103]106,110,112 However, a substantial number (n = 44) were classed as unclear, due to lack of sufficient information in the paper to permit detailed assessment of whether or not an important risk of bias existed, or due to insufficient rationale or evidence that an identified problem had introduced serious levels of bias to the study. 43,[57][58][59][60]65,66,68,69,72,73,[75][76][77][78]…”
Section: Allocation Concealmentmentioning
confidence: 99%
“…57,60,61,63,64,66,67,73,76,78,[80][81][82][83][84][85]88,89,93,98,99,102,103,[105][106][107][108]112,118 Thirty studies did not provide sufficient information to allow a judgement of low or high risk and were therefore classed as unclear. 13,[41][42][43]58,59,62,65,[68][69][70][71]74,75,77,79,90,91,[94][95][96][97]100,…”
Section: Allocation Concealmentmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Two prospective randomized studies have confirmed that steroid treatment is superior to standard antiemetic therapies. 4,5 We have previously reported that steroid therapy is uniformly effective in a consecutive series of women with severe hyperemesis as defined by the criterion of weight loss of .5% of pre-pregnant weight. 6 However, knowledge about steroid dosage regimens to achieve control of hyperemesis is not widespread.…”
Section: Introductionmentioning
confidence: 99%